National Disaster Risk Management Policy - Malawi Government: Ministry of Finance, Economic Planning and Development (Malawi Government, 2021)
Malawi faces a number of disasters, both natural and human-made which include floods, drought, stormy rains, strong winds, hailstorms, landslides, earthquakes, pest infestations, diseases outbreaks, fire and accidents. The intensity and frequency of disasters has been increasing, in light of climate change, population growth, urbanisation and environmental degradation. Disasters disrupt people’s livelihoods, endanger human and food security, damage infrastructure and hinder socio-economic growth and development. Disasters also increase the poverty of rural and urban households and erode the ability of the national economy to invest in key social sectors which are important to reducing poverty. It is, therefore, important to address disaster risks for the socio-economic development of the country. Disaster risk management, together with social support, is considered within theme three “Social Support and Disaster Risk Management” of the Malawi Growth and Development Strategy II (MGDS II); a national development strategy that ensures that resources are targeted towards priority areas thereby contributing to the attainment of sustainable development. The development of the National Disaster Risk Management (NDRM) Policy is a major step towards achieving sustainable development through ensuring that disaster risk management is integrated in development planning by all sectors in the country. The policy will also facilitate the effective coordination of disaster risk management programmes in the country. It highlights a set of key priority areas and strategies for making Malawi a nation resilient to disasters. It also provides a common direction to all government, non-governmental organisations, private sector organizations, media and development partners at national and local levels on how to effectively implement disaster risk management programmes and activities. I commend all stakeholders for their commitment in the development of this policy. This policy calls upon all sectors and stakeholders to pursue a proactive and integrated way of reducing risks to hazards through sustainable, innovative and realistic strategies with strong partnerships and networks. The government is committed to ensure implementation of the policy so as to significantly reduce the social, economic and environmental impacts of disasters in the country. It is, therefore, my sincere hope that all stakeholders in the country will align their activities towards this policy in order to ensure that resilience to disasters is built at national, local and community levels.